The oestrous cycle, mating practices, conception rates and fetal losses in thoroughbreds in the Eastern Cape Province - Marlow, Christopher Harry Baden (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Agric.)) -- University of Stellenbosch, 1983..